Between faith and unbelief: Notes on E. D. Pazderin’s manuscript “Memoirs” - Tatarintseva, Margarita P. (The New Research of Tuva, 2021)
The article takes a close look at E. D. Pazderin’s (1902–1980) “Memoirs” — a manuscript describing the life of Russian Old Believer settlers in Tuva, in the upper reaches of the Maly Yenisei in the first half of the 20th century. Since 1977, the manuscript has been preserved in the research archive of Tuvan Institute of Humanities and Applied Socio-Economic Research under the Government of the Republic of Tuva. Born to an Old Believer family, the author provided a detailed narrative of his life in Old Believer community from the 1920s to the 1940s, of the subsequent evolution of his religious views and his ultimate transformation into an activist, a propagandist who condemned “religious prejudice”. Besides the author’s biographical twists, the manuscript covers a multitude of facts, events and developments in Verkhovye, which were unknown to historical science from any other source. In describing the lifestyle of the Old Believers’ community, Pazderin focuses on their confessional non-uniformity, their self-sustainability under new living conditions, on their contacts with the indigenous population, on protests and self-defense of Old Believers against the anti-religious policy of the government (which Old Believers saw as the Anti-Christ). Pazderin provides an explanation and assessment to every detail, often reassessing them later. The author of the “Memoirs” was always beset with doubts and hesitation, which ultimately led to his loss of faith, although he never moved out of his Old Believer village, where he lived until his death. In this article, Pazderin’s memoirs are compared with another manuscript by a non-professional author — N. G. Sidorkina’s “Zapovednaia vera. Kniga zhitiia i stradanii symskikh staroobriadtsev” [“Sacred faith. The book of life and sufferings of the Old Believers of Sym”]. Also an Old Believer, Pazderina evolved in the opposite way: from unbelief she moved to strong devotion.